Analisa Kebutuhan pada Pembelajaran Membaca Permulaan di Pendidikan Anak Usia Dini - Fida Chasanatun; sunardi sunardi; Joko Nurkamto; Asrowi Asrowi (Jurnal Penelitian Pendidikan, 2015)
This research is constituted by the application of teaching early reading literacyimpplemented in some schools across ex-residency Madiun. The teaching shouldimplement character based teaching as an introduction into the ability of early readingliteracy. That is carried out for various reasons, for example, the demands of the students’parent, the demands of the furhter school level, commercial reasons, and so forth. Thisstudy implemented a combination of research methods. Initiated into content validityanalysis or analysis of existing learning contents based on theory of study the effectivenessof learning, then combined with observations and school interviews and literature study,narrowing the findings to lead the new concept for early reading literacy learning. 40Schools being randomly selected were used in this research in the ex-residency Madiun.These research findings illustrated the true condition about the application of early readingliteracy learning in the field. Referring to the findings of questionnaires and interviews,the teaching of early reading literacy was delivered in additional learning program.This made it possible to avoid infringement of the government rules about unpermittedlearning at that level. Besides, those were found the lack of some language componentsthat allows the imperfectness of introduction and readiness of children to acquaint thelanguage. Furthermore, it lacked involvement of children playing environment both athome and at school for learning outcome optimality. Finally those findings were used asa reference to create an integrated learning tools in the children’s playground in the formof teachers and parents’ guide.